Animal Symbolicum Dalam Adat Jalatn Lome Jaih: Kunci Misi Gereja Katolik Di Tanah Krio, Ketapang, Kalimantan Barat - Parto, Hilarion Gerri; Ajung, Florensius; Nadila, Yulita (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2025)
This study focuses on understanding Animal Symbolicum in the Jalatn Lome Jaih tradition of the Dayak Krio community in Ketapang, West Kalimantan, and its role in supporting the Catholic Church’s mission to harmonize religious teachings with local culture. In Indonesia, the relationship between religion and local culture often faces challenges, particularly in communities with strong customary traditions such as the Dayak Krio. Jalatn Lome Jaih is a tradition related to the life cycle—from birth, marriage, to death—rich in cultural and spiritual symbolism. The Catholic Church, in its mission in Tanah Krio, requires an adaptive approach to ensure its teachings are more accepted by the local community without disregarding their cultural identity. This study employs a literature review and an analytical approach, utilizing Ernst Cassirer’s concept of Animal Symbolicum to explore customary symbolism as a medium of communication in the dialogue between religion and culture. The findings reveal that several symbols in Jalatn Lome Jaih, such as the use of water in nurutn manik, which resembles the sacramental meaning in baptism, or the concept of ancestral reverence in batipak baluhak, which aligns with prayers for the souls in the Catholic Church, can serve as common ground to enrich the spirituality of the Dayak Krio community. Thus, customary symbolism can function as a communication medium that enables a more contextual and inclusive pastoral approach in Tanah Krio.